Analisis Kemampuan Pemecahan Masalah Siswa Madrasah Tsanawiyah Kelas VII pada Materi Himpunan - Adifta, Engsas Diniati; Maimunah, Maimunah; Roza, Yenita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The objectives of this research are to describe the level of student problem solving skills and types of errors made by students. The research method used descriptive qualitative. The subject consisted of 9 students who were categorized based on student academic ability selected from 18 students of class VII MTs Nurul Bilad in academic year 2019/2020. Research instrument used 3 items of set materials. The data analysis techniques were in the form of qualitative and quantitative descriptive analysis. The result of the research showed that the student problem solving skills of class VII MTs Nurul Bilad was still relatively low. Research results obtained as a whole based on student problem solving skill indicators which were indicators of understanding problems (77,8%), making a solution plan (0%), implementing strategies to solve problems (51,8%) and explaining or interpreting the results of problem solving (14,8%). Meanwhile, the concept errors were mostly found from students with low academic ability. These errors resulted in students’ misinterpreting the problems, so that the principles used would be also wrong. There were some among students comitting errors in operation (procedure).